2005
DOI: 10.1098/rspb.2005.3052
|View full text |Cite
|
Sign up to set email alerts
|

The colour of fitness: plumage coloration and lifetime reproductive success in the tawny owl

Abstract: We studied variation in plumage colour and life history in a population of tawny owls (Strix aluco) in southern Finland, using 26 years of data on individually marked male and female owls. Colour was scored on a semi-continuous scale from pale grey to reddish brown. Colour scoring was repeatable and showed a bimodal distribution (grey and brown morph) in both sexes. During the study period, colour composition was stable in the study population in both sexes. The sexes did not mate assortatively with respect to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
141
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(161 citation statements)
references
References 30 publications
5
141
2
Order By: Relevance
“…Female colour polymorphisms have also been reported in fish (McKinnon et al 2000, Pierotti andSeehausen 2007) and several species of birds (Bleiweiss 2001, Roulin et al 2003, Brommer et al 2005. In three-spine sticklebacks Gastrosteus aculeatus, the intensity of orange-red throat colouration appears to be non-randomly associated with migratory behaviour, since there are differences between stream-resident and anadromous females, whereas no such differences were found between males (McKinnon et al 2000).…”
Section: Female Sexual Polymorphisms In Natural Populationsmentioning
confidence: 91%
See 2 more Smart Citations
“…Female colour polymorphisms have also been reported in fish (McKinnon et al 2000, Pierotti andSeehausen 2007) and several species of birds (Bleiweiss 2001, Roulin et al 2003, Brommer et al 2005. In three-spine sticklebacks Gastrosteus aculeatus, the intensity of orange-red throat colouration appears to be non-randomly associated with migratory behaviour, since there are differences between stream-resident and anadromous females, whereas no such differences were found between males (McKinnon et al 2000).…”
Section: Female Sexual Polymorphisms In Natural Populationsmentioning
confidence: 91%
“…Thus, female colour morphs are likely to be targets of direct selection with male mating behaviour playing key role, as is the situation in butterflies and damselflies. In tawny owls Strix aluco, there is a colour polymorphism that is present in both males and females: reddish-brown and grey phenotypes (Roulin et al 2003, Brommer et al 2005. The ecological and physiological consequences of these colour differences is uncertain but they may be related to temperature tolerance.…”
Section: Female Sexual Polymorphisms In Natural Populationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the Common Guillemot genes for bridling may have a pleiotropic effect, such that color dimorphism may be associated with another property that is the real target of selection. Several studies of both birds and other animals have suggested that differential performance of morphs across environments are caused by genetic co-variation between coloration and a physiological or behavioral trait (Roulin 2004, Brommer et al 2005, Ducrest et al 2008, Piault et al 2009). However, our study gives no support for any physiological differences related to temperatures.…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, tawny owls show continuous variation in melaninbased plumage coloration (from light to dark reddish; for pictures, see Da Silva et al, 2013), the expression of which is strongly genetically controlled and not sensitive, or only weakly so, to environmental conditions (Brommer et al, 2005;Gasparini et al, 2009;Emaresi et al, 2013). Interestingly, differently coloured adult males display alternative trade-off resolution and life histories (Emaresi et al, , 2014.…”
Section: Introductionmentioning
confidence: 99%